The Molecular Mechanism of α-Resorcinol's Asymmetric Crystal Growth from the Melt - Ectors, Philipp; Sae-Tang, Wang; Chatchawalsaisin, Jittima; Zahn, Dirk; Anwar, Jamshed (Crystal Growth & Design, 2015)
Polar crystals are characterized by an axis that has a nonzero dipole due to the nature of the molecular packing. For these crystals, the growth rates of the faces delineating the polar axis are generally expected to be equal. Recent experiments, however, have revealed a few exceptions where the growth of these faces from the vapor phase is asymmetric, a notable case being crystals of resorcinol. Here, we present the mechanics of resorcinol crystal growth from the melt for the hemihedral faces (011) and (01̅1̅) delineating the polar axis as revealed by molecular dynamics simulations. The simulations reveal asymmetric growth consistent with experiment. The asymmetry is attributed to the slow-growing (011) face being less able to direct the correct alignment of the oncoming molecules and the presence of an alternate resorcinol conformation that readily incorporates into the lattice at this surface, serving to poison and retard subsequent growth. Putting the issue of the rogue conformation aside, the identified factors that influence molecular recognition are considered to be applicable to other polar crystals, which suggest asymmetric growth along the polar axis to be a common feature.
EAM Import::2019-03-12